Towards understanding medical residents' practices and perceptions of end-of-life care implications for training in ethics - Dela Cruz, Ma. Henrietta Teresa O.
Background: Advances in resuscitative measures and the use of advanced life support devices have raised the issue of how physicians in residency training programs approach the ethical deliberation of the patients' and family's decisions for end-of life care. Methods: Interviews of 12 resident physicians in Internal Medicine were conducted in 2 governments, 3 private and 2 academic training hospitals. A follow-up survey of 92 residents in various year levels in the same hospitals was done. Results: Residents in training had some experience with discussions on non-resuscitation (60%) and withdrawal of treatment (54%) but less has ever given orders for withdrawal of treatment (54%) but less had ever given orders for withdrawal of feeding (25%). More residents in government hospitals claimed greater confidence in handling various discussions for non-resuscitation (70%) , disclosure of terminal illness with patients (71%), discussing patients' throughts and fears (60%). Some residents were older (53%), with poor functional capacity (70%) and with a lack of resources (47%). Residents who had previous experience with ordering non-resuscitation were more likely to agree that families of terminally ill incompetent patients whose chances of recovery of functional capacity are nil should be advised against resuscitation (OR=5.436, p=.020). There were no significant associations between religion, sex, age, and type of institute with decisions for non-resuscitation. Conclusions: Resident generally handle complex issues and problems with the patient's autonomy and true benefit in mind, although skills to open and and broaden the discussion and provide assistance for patients and relatives in compassionate decision making may open doors for more meaningful rather than defensive approaches. The disadvantaged situation of patients and families facing end-of-life decisions in the setting of poverty asks for the physcian to actively and compassionately carry out a duty to remedy the unjust situation.
Theses--(Master of Science in Bioethics) UPCM
Keywords: Ethics, Medical; Internship and Residency